Vasoactive prostanoids in normal and hypertensive pregnancies - Railton, Angela (Department of Obstetrics and Gynaecology, 2026)
The role of vasoactive prostanoids in the pathogenesis of the hypertensive diseases in pregnancy is currently under debate. Studies have demonstrated a generalised deficiency of vasodilator prostanoids, particularly prostacyclin and a disturbance of the vasodilator to vasoconstrictor balance in pre-eclampsia. The first part of this thesis reviews the literature with regard to the pathophysiology of gestational hypertension and the factors and mechanisms which may be responsible for the causation of the disease, with particular reference to the role of the prostanoids.